Somatotype, diet and nutritional status of women - Drywień, Małgorzata E.; Frąckiewicz, Joanna; Górnicka, Magdalena; Ważna, Beata; Zielińska, Paulina; Wójcik, Katarzyna; Kulik, Stanisław (Anthropological Review, 2017)
The relationship between energy value and nutrients intake and the body shape and size parameters (weight, height, waist and hip circumferences) has become an interesting research area for nutritionists and dieticians. The aim of this study was to determine the relationship between the body shape and size parameters (weight, height, waist and hip circumferences), somatotype (according to the Rohrer (RI) index) and energy value and nutrients intake of women. The study was conducted in 2014 and 2016 on 148 female volunteers aged 57–88 from the Mazovian and Lublin province (Poland). Sample selection was targeted at elderly people with different body types. The exclusion criteria were: multi-organ failure, cancer and disability. Then among the subjects, a survey was conducted, that included demographic data, lifestyle, health status and vitamins and minerals supplements use. Food intake has been assessed using a 3-day dietary food records. The somatotype was determined using the RI with the Curtis key, classifying the subjects as ectomorphic (n=30), mesomorphic (n=31) and endomorphic (n=87). The somatotype was significantly related to place of residence, physical activity, waist and hip circumference, WHR and BMI index, total protein intake, animal protein intake, vitamin E intake (p≤0.05) and to fat, phosphorus and thiamine intake (p≤0.1). The obtained results showed that the place of residence, physical activity, chronic diseases, the use of specialized diet, body weight fluctuations, BMI and WHR were different depending on the somatotype in the examined group of women. Endomorphic subjects had significantly greater waist and hip circumference and diastolic blood pressure compared to the other somatotypes. The somatotype had only a significant effect on total protein, animal protein and vitamin E intake, and ectomorphic elderly women may be particularly susceptible to nutrient deficiencies. Due to the risk of macronutrient, vitamin and mineral deficiencies in the diets of the examined women, it seems necessary to educate this group as well as caregivers and doctors in the area of nutrition adapted to the needs of the elderly.